The End of the Epitymbia Section in the Milan Papyrus and Pairing of Epigrams in Posidippus - Kazanskaya, Maria (Hyperboreus, 2019)
The article analyses the concluding epigrams of the ᾿Επιτύμβια section of the Milan papyrus (P. Mil. Vogl. VIII, 309) containing a collection of poems attributed to Posidippus of Pella. It is argued that Ep. 59 and 60 were intentionally paired by the poet and meant to be read together. The circumstances evoked in the epitaph of Menestrate (Ep. 59) show an old woman who lived a life close to Solon’s ideal (Sol. fr. 27 and fr. 20 West), while the details of the epitaph of Mnesistratos (Ep. 60) present a jovial man who died at the age of sixty, at the very onset of old age, a fate that Mimnermus had coveted for himself (Mimn. fr. 6 West). Ep. 59 and 60 would seem then to illustrate the opposed positions on the best moment to die that were associated with Solon’s debate with Mimnermus; once this intertextual link is recognized, the last epigram of the ᾿Επιτύμβια section, epitaph of Aristippos (Ep. 61) can be read as Posidippus’ own take on the question of what can be considered a happy old age (εὐγηρία).